The mists of Avalon - Bradley, Marion Zimmer (New York : Ballantine Books, 1982)
When Morgan le Fay (Morgaine) has to sacrifice her virginity during fertility rites, the man who impregnates her is her younger brother Arthur, whom she turns against when she thinks he has betrayed the old religion of Avalon.
"A Del Rey book."
Accelerated Reader/Renaissance Learning
Keywords: Arthurian romances; Great Britain -- History -- Anglo-Saxon period, 449-1066 -- Fiction